1998
DOI: 10.1016/s1043-4542(98)90003-0
|View full text |Cite
|
Sign up to set email alerts
|

Peak and nadir experiences and their consequences described by pediatric oncology nurses

Abstract: Pediatric oncology nurses experience role-related stressors, some of which are inherent to the speciality, and their consequences. Despite these difficulties, nurses continue in the specialty. One variable that helps to explain their continued commitment is "meaning", or what pediatric oncology nurses find to be most significant and satisfying in their roles. One technique for determining meaning in a role is to inquire about the peak (significant and positive) and nadir (significant and negative) role-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The opening questions were: 'Please describe one or more peak experiences you have had when caring for children in pain' and 'Please describe one or more nadir experiences you have had when caring for children in pain' (Olson et al 1998). During the interview, probing was used in order to encourage the nurse to respond to the questions as comprehensively as possible.…”
Section: Data Collectionmentioning
confidence: 99%
“…The opening questions were: 'Please describe one or more peak experiences you have had when caring for children in pain' and 'Please describe one or more nadir experiences you have had when caring for children in pain' (Olson et al 1998). During the interview, probing was used in order to encourage the nurse to respond to the questions as comprehensively as possible.…”
Section: Data Collectionmentioning
confidence: 99%
“…Childhood cancer is a distressing experience both for family and healthcare professionals. Various studies have explored parents’ experiences in terms of marital and parental quality of life during and after their child's treatment (Bally et al., ; Barling, Stevens, & Davies, ; Bishop, Stedmon, & Dallos, ; Brody & Simmons, ; Robert et al., ; Wong & Chan, ) and an increasing number of studies have examined the lived experience of work‐related stress and grief among paediatric oncology nurses and physicians (Conte, ; Enskär, ; Olson et al, ; Stenmarker, Palmérus, & Màrky, ). With some notable exceptions, children's perspective is rarely ever discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Often due to their emotional involvement with families at a child's end of life, nurses experienced grief and feelings of loss from their patients' deaths and from bearing witness to families' suffering (Davis et al, 1996;Papadatou, Bellali, Papazoglou, & Petraki, 2002;Papadatou, Martinson, & Chung, 2001;Rushton et al, 2006;Yam, Rossiter, & Cheung, 2001). Despite contributing to their grief, nurses in these studies viewed emotional support to families as an essential aspect of their practice and constitutive to their work being rewarding and meaningful Engler et al, 2001;Olson et al, 1998;Papdatou, Bellali, et al;Papadatou, Martinson, et al;Rashotte, Fothergill-Bourbannais, & Chamberlain, 1997). These nurses experienced personal costs from the intensity of their work, such as feeling distress, forming close attachments, and grieving the loss of a child.…”
Section: List Of Figures Andmentioning
confidence: 99%
“…Families report a higher quality of care when they are given emotional support and individualized attention from health care providers caring for their child at the end of life (Heller & Solomon, 2005;Macdonald et al, 2005). Studies found that nurses derived meaning from their work through their emotional involvement with families (Davies et al, 1996;Olson et al, 1998;Papadatou et al, 2001;Rashotte et al, 1997;Yam et al, 2001). Nurses view their emotional support as integral to their role caring for children at the end-of-life and their families Engler et al, 2001;Olson et al;Papdatou et al, 2001;Rashotte et al).…”
Section: Nurses Caring For Dying Childrenmentioning
confidence: 99%
See 1 more Smart Citation